2017
DOI: 10.1038/ncomms15719
|View full text |Cite
|
Sign up to set email alerts
|

Cryogenic strength improvement by utilizing room-temperature deformation twinning in a partially recrystallized VCrMnFeCoNi high-entropy alloy

Abstract: The excellent cryogenic tensile properties of the CrMnFeCoNi alloy are generally caused by deformation twinning, which is difficult to achieve at room temperature because of insufficient stress for twinning. Here, we induced twinning at room temperature to improve the cryogenic tensile properties of the CrMnFeCoNi alloy. Considering grain size effects on the critical stress for twinning, twins were readily formed in the coarse microstructure by cold rolling without grain refinement by hot rolling. These twins … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
71
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 338 publications
(81 citation statements)
references
References 44 publications
1
71
0
Order By: Relevance
“…Micro-twining mechanism at cryogenic temperatures Micro-twins have been experimentally observed in most HEAs during deformation, [2][3][4]8,15 particularly at 77 K, and are regarded as a probable reason for excellent tensile properties at 77 K. Previous studies claimed that the low stacking fault energy (SFE) of HEAs is one of the probable reasons for the micro-twinning. 27,28 However, it is not fully understood why HEAs have a low SFE.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Micro-twining mechanism at cryogenic temperatures Micro-twins have been experimentally observed in most HEAs during deformation, [2][3][4]8,15 particularly at 77 K, and are regarded as a probable reason for excellent tensile properties at 77 K. Previous studies claimed that the low stacking fault energy (SFE) of HEAs is one of the probable reasons for the micro-twinning. 27,28 However, it is not fully understood why HEAs have a low SFE.…”
Section: Resultsmentioning
confidence: 99%
“…4 Even though most HEAs have equiatomic or near equiatomic compositions, it is believed that the equiatomic composition would not be the optimum composition for a wide range of material properties. [5][6][7][8][9][10] To improve a specific material property, one may have to change the alloy composition from the equiatomic composition. Indeed, there have been many efforts to improve the facecentered cubic (fcc) single-phase stability or mechanical properties of the CoCrFeMnNi HEAs by adjusting the composition.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The VCrMnFeCoNi HEA exhibits excellent cryogenic mechanical properties with a yield strength of %1 GPa and elongation up to 46%. [59] The HE nitride film of SiTiVAlCrNb shows remarkable thermal stability by retaining its nanostructure even after annealing at 1000 C for 5 h. [75] The [76] In addition, a wide range of multicomponent amorphous alloys based on equiatomic substitution has been investigated. [77][78][79][80][81][82] In one of the study, the addition of Nb is reported to increase the thermal stability of amorphous phase.…”
Section: Introductionmentioning
confidence: 99%